Pendugaan Umur Simpan Ikan Patin Salai Menggunakan Metode Akselerasi Dengan Kemasan HDPE dan Teknik Pengemasan Aluminium Foil - Dewi Fortuna Ayu; Raswen Efendy; Yanti Nopiani; Edo Saputra; Syafitri Haryani (Agricultural Faculty, 2022)
The goal of this research was to estimate the shelf life of salai catfish using the ASLT (Accelerated Shelf-Life Testing) method with high-density polyethylene (HDPE) plastic, vacuum aluminum foil, and non-vacuum aluminum foil. By storing the salai catfish for thirty days at different temperature levels, namely 30, 35, and 40°C, the acceleration method was used to predict the shelf life. Changes in rancidity sensory and thiobarbituric acid (TBA) levels were observed. The obtained data were analyzed using linear regression to show the relationship between storage time and the measured variables. Furthermore, the Arrhenius method was used to calculate the shelf life of salai catfish in order to compare the quality degradation of salai catfish. The best result was obtained in the treatment of salai catfish with vacuum aluminum foil was 32,56 days at 30°C based on the TBA test. The regression equation were y= -2875,7x + 5,2812, R2= 0,9855.